Marine Fouling Release Performance of Amphiphilic Carboxybetaine Perfluoropolyether Methacrylate Polymer Coatings - Florian Koschitzki; Onur Özcan; Robin Wanka; Marc Krisam; Axel Rosenhahn (Advanced Materials Interfaces)
Abstract Amphiphilic polymer systems have been demonstrated to be an effective and environmentally friendly approach to combat the challenges of biofouling, especially in the real ocean environment. A variety of polymer compositions containing fluorophilic perfluoropolyether (PFPE) urethane dimethacrylate and zwitterionic carboxybetaine methacrylate (CBMA) are in situ copolymerized across a broad concentration range and anchored to chemically functionalized substrates by grafting‐through polymerization. Dynamic accumulation assays with the marine diatom Navicula perminuta and the marine bacterium Cobetia marina revealed an enhanced antifouling performance in most of the amphiphilic polymer mixtures when zwitterionic units are combined with hydrophobic PFPE compounds. It is noticed that the resulting polymer networks still possess enough orientational freedom to quickly rearrange in the presence of water. It is further observed that several of the very hydrophilic formulations and some of the moderately hydrophobic formulations exhibit low fouling against the marine fouling organisms Navicula perminuta and Cobetia marina. This correlated with increased surface roughness and the ability for underwater rearrangement. Furthermore, it is discussed whether the probability that highly hydrated hydrogels, which appear sponge‐like, may create a diffuse interphase which promotes the incorporation of silt. Latter is counteracted by the hydrophobic PFPE building blocks in the amphiphilic coatings.